2014
DOI: 10.1063/1.4895549
|View full text |Cite
|
Sign up to set email alerts
|

CO2 and C2H2 in cold nanodroplets of oxygenated organic molecules and water

Abstract: Recent demonstrations of subsecond and microsecond timescales for formation of clathrate hydrate nanocrystals hint at future methods of control of environmental and industrial gases such as CO2 and methane. Combined results from cold-chamber and supersonic-nozzle [A. S. Bhabhe, "Experimental study of condensation and freezing in a supersonic nozzle," Ph.D. thesis (Ohio State University, 2012), Chap. 7] experiments indicate extremely rapid encagement of components of all-vapor pre-mixtures. The extreme rates ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…Within the five independent simulations at each temperature, we observed a total of four hydrogen-interchange events at 250 K and eight hydrogen-interchange events at 260 K, which correspond to a hydrogen-interchange rate of ∼10 4 s –1 per water molecule, whereas hundreds of such events, which corresponds to a hydrogen-interchange rate of ∼10 6 s –1 per water molecule, can be observed at the high temperature of 300 K. With the measured the hydrogen-interchange rate, we can estimate the associated free energy of activation using eq . Figure shows the linear regression results of the measured hydrogen-interchange rates (ln­( k / T )) versus temperatures (1/ T ), from which we can calculate that the 95% confidence interval for the rate of the hydrogen interchange is 1.3 × 10 5 –2.4 × 10 5 s –1 per water molecule, and the 95% confidence interval for the associated free energy of activation is 38.2–39.4 kJ/mol at 270 K. These values are comparable to previous results from all-vapor experiments, supersonic nozzle experiments, and thermodynamics calculations , of clathrate hydrates with hydrogen-bonding guests but under much lower temperatures, indicating the effects of the hydrogen-bonding guests on inducing the defect formation and accelerating the mass diffusion in gas hydrates. Note while previous experimental studies using NMR techniques have studied the water reorientation processes within gas hydrate systems, for example, the activation energy of water reorientations in THF hydrates is determined to about 31 kJ/mol, ,, the particular type of water reorientations discussed in this paper may not be identified directly in these NMR experiments where all the possible water orientations are sampled over time.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Within the five independent simulations at each temperature, we observed a total of four hydrogen-interchange events at 250 K and eight hydrogen-interchange events at 260 K, which correspond to a hydrogen-interchange rate of ∼10 4 s –1 per water molecule, whereas hundreds of such events, which corresponds to a hydrogen-interchange rate of ∼10 6 s –1 per water molecule, can be observed at the high temperature of 300 K. With the measured the hydrogen-interchange rate, we can estimate the associated free energy of activation using eq . Figure shows the linear regression results of the measured hydrogen-interchange rates (ln­( k / T )) versus temperatures (1/ T ), from which we can calculate that the 95% confidence interval for the rate of the hydrogen interchange is 1.3 × 10 5 –2.4 × 10 5 s –1 per water molecule, and the 95% confidence interval for the associated free energy of activation is 38.2–39.4 kJ/mol at 270 K. These values are comparable to previous results from all-vapor experiments, supersonic nozzle experiments, and thermodynamics calculations , of clathrate hydrates with hydrogen-bonding guests but under much lower temperatures, indicating the effects of the hydrogen-bonding guests on inducing the defect formation and accelerating the mass diffusion in gas hydrates. Note while previous experimental studies using NMR techniques have studied the water reorientation processes within gas hydrate systems, for example, the activation energy of water reorientations in THF hydrates is determined to about 31 kJ/mol, ,, the particular type of water reorientations discussed in this paper may not be identified directly in these NMR experiments where all the possible water orientations are sampled over time.…”
Section: Resultssupporting
confidence: 83%
“…The transient defects generated during these processes may facilitate guest rotational and translational motions in the gas hydrate cages and hence have implications for the unusual behavior of the thermal conductivity and mechanical properties of gas hydrates. , Note similar rotation processes have been observed in ice Ih when the central water molecules are surrounded by a Bjerrum L-type defect . This rotation process is also essential to the proton transport and the isotopic exchange processes as demonstrated before. ,,, It has been shown that the hydrogen-bonding guests, such as small ether molecules, H 2 S, etc., can enhance the defect concentration in gas hydrates and catalyze the formation of gas hydrates, , which are consistent with the all-vapor gas hydrate formation experiments with various guest molecules. In future studies it would be interesting to investigate the possible role of the guest molecules in inducing and stabilizing the transient defects in gas hydrates.…”
Section: Resultssupporting
confidence: 74%
“…The acetylene classical s-c frequency is decreased slightly from the gas-phase value of 3289 to ∼3280 cm –1 , but is downshifted another ∼30 cm –1 upon bonding to the cage wall . Nevertheless, that downshift is small compared to the ∼100 cm –1 amount for C 2 H 2 dissolved in oxygenated organics, or within the corresponding heterogeneous dimers . The large shift is a testimony to an acidity of the acetylene hydrogen as well as the strength of its electron-acceptor charge-transfer interactions .…”
Section: Experimental Results and Discussionmentioning
confidence: 88%
“…The premixing was completed with addition of ∼100 Torr of He(g). During the present study, the vapor premixtures at different times contained (a) THF alone, (b) THF with HCN, (c) THF with HCl/DCl, (d) THF with HCN followed by HCl/DCl added in a second pulse (as previously described in a study of the droplet compositions), 23 (e) THF with HCl with HCN added in a second pulse, (f) all three guests in a single pulse, (g) THF alone followed by HCN in the second pulse, and (h) THF alone followed by HCl. It is noteworthy that guest molecules of any second pulse are not premixed with vapors of the other guests but occupy the CH particles only through rapid transport into pre-existing CH aerosol particles available from the first pulse.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…Experimental studies of clathrate nucleation also reflect a wide variety of pathways by which it can occur. For example, Devlin et al 14 have shown that hydrates can form from all-vapour mixtures at sufficiently large driving forces (which are comparable or greater than those used in MD simulations) via the formation of nanodroplets. Hawtin et al 15 reviewed the use of technologies such as neutron scattering, [16][17][18] nuclear magnetic resonance, and X-ray tomography 19 .…”
Section: Iv)mentioning
confidence: 99%